Use of Ni Catalysts Supported on Biomorphic Carbon Derived From Lignocellulosic Biomass Residues in the Decomposition of Methane - Azuara, Manuel; Latorre, Nieves; Villacampa, José I.; Sebastian, Victor; Cazaña, Fernando; Romeo, Eva; Monzón, Antonio (Frontiers in Energy Research, 2019)
In this work, we present the results of production of carbonaceous nanomaterials by decomposition of methane on a catalyst of Ni supported on a Biomorphic Carbon. The catalyst was prepared by thermal decomposition in a reductive atmosphere of vine shoots previously impregnated with the Ni precursor. In order to optimize the reaction productivity and selectivity, the effect of the main operational conditions (reaction temperature and feed composition) has been studied in a thermobalance. The main textural properties, BET area of 63 m2/g and 56% of microporosity, of the catalyst synthesized indicates that these materials are suitable for gas-phase reactions even in harsh conditions. Thus, the catalyst has proved to be active in the synthesis of carbon nanofibres and graphene related materials at elevated temperatures. The productivity, type and quality of the carbonaceous nanomaterials obtained are deeply dependent on the operating conditions during the reaction. As an important fact, is has been obtained that the reaction temperature strongly affects the type of the nanomaterial produced. Thus, it is produced CNFs of bamboo type at temperatures until 850 ºC. Above this critical temperature, it is mainly obtained nanolayers of graphitic nature. The characterization results indicate that the highest quality graphenic materials were obtained operating at 950 °C with 14.3 % of CH4 and 14.3 % of H2. The kinetic model used to analyze the experimental data is based on the more relevant stages of the mechanism of reaction.